Some aspects of continuity and discontinuity between late antiquity and the early middle ages in Dalmatia - Jurković, Miljenko (Array, 1997)
The former roman province Dalmatia was by the time the Croats settled in the early middle ages a flourishing part of the roman empire. In that transitional period between the end of the 6th century and the end of the 8th, so far as we now know, no distructions of a greater scale had happened. Therefore, the Croats were able to settle in a province with a high level of urbanisation, and, what is more important, a wholy christianised province. That enabled them to fully embrace not only Christianity but also the way of life, technics, and so on. Continuity therefore played an important role in the formation of the first croatian medieval states.